If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9a + -7a = 0 Combine like terms: 9a + -7a = 2a 2a = 0 Solving 2a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '2'. a = 0 Simplifying a = 0
| (2z+5)(3-z)=0 | | 7ln(x+5)-9ln(x)= | | 8x+8(-5+3x)=5 | | (h+9)=2(h+9)+-6 | | 2(x-3)+x+4=9-2x+1+x | | M^2+7m+p^2=0 | | y(h+9)=2(h+9)+-6 | | 2x-34=20 | | 2t^3+t-3=0 | | m+m+9=3+m | | 21=-5k | | M^2+7m=p^2 | | 20x-5+17-3x= | | 21=-5+k | | 70+70+w*2=340 | | 5x+3-37=6x+23-8x | | -4x+-2.363636364=-2 | | 12=44x-12 | | 0.5+0.25y-3y=7 | | 0.5cos(x)=sin(2x) | | Y=1.1x^2+4.2x+4.9 | | 2x^2+x=69 | | y-4.5=12.2 | | x^2+(y-5)=30 | | 4x^2(-5+-15x+x^2+3x^3)= | | 8.1=a-(-2.4) | | 0.3x^2-2x+3.6=0 | | -5x+7=-8+9x | | 42u=4.66666666667 | | -6x-3=4x+7 | | 50=10x+15-3x | | g+-7=21 |